2019
DOI: 10.1016/j.tranon.2018.08.018
|View full text |Cite
|
Sign up to set email alerts
|

Combined Metabolo-Volumetric Parameters of 18F-FDG-PET and MRI Can Predict Tumor Cellularity, Ki67 Level and Expression of HIF 1alpha in Head and Neck Squamous Cell Carcinoma: A Pilot Study

Abstract: BACKGROUND: Our purpose was to evaluate associations of combined 18F-FDG-PET and MRI parameters with histopathological features in head and neck squamous cell carcinoma (HNSCC). METHODS: Overall, 22 patients with HNSCC were acquired (10 with G1/2 tumors and 12 with G3 tumors).18F-FDG-PET/CT and MRI was performed and maximum standardized uptake value (SUVmax), total lesion glycolysis (TLG) and metabolic tumor volume (MTV) were estimated. Neck MRI was obtained on a 3 T scanner. Diffusion weighted imaging was per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 35 publications
(74 reference statements)
1
15
0
Order By: Relevance
“…It has already been reported that SUV max is related to K ep P10, and that P25 and TLG tended to be related to K ep P25 and K trans P10 in primary HNSCCs [19]. Moreover, it has been suggested that the evidence of these correlations may also depend on tumor grading, with G1/G2 PTs showing significant associations, while no correlations are evident in G3 PTs [19,13]. This may partially explain the lack of correlations in PTs emerging from our study: in our cohort, HPV-negative OPSCCs were predominately G3 (13/19 patients) while no grading system currently exists for HPV-positive OPSCCs according to the American Joint Committee on Cancer Staging Manual [30].…”
Section: Plos Onementioning
confidence: 94%
See 1 more Smart Citation
“…It has already been reported that SUV max is related to K ep P10, and that P25 and TLG tended to be related to K ep P25 and K trans P10 in primary HNSCCs [19]. Moreover, it has been suggested that the evidence of these correlations may also depend on tumor grading, with G1/G2 PTs showing significant associations, while no correlations are evident in G3 PTs [19,13]. This may partially explain the lack of correlations in PTs emerging from our study: in our cohort, HPV-negative OPSCCs were predominately G3 (13/19 patients) while no grading system currently exists for HPV-positive OPSCCs according to the American Joint Committee on Cancer Staging Manual [30].…”
Section: Plos Onementioning
confidence: 94%
“…Considering the volume of data that can be derived from both histology and functional imaging, radiologists and clinicians should be aware of the different potential roles of several biomarkers with respect to specific clinical end points. To this purpose, a number of reports have recently evaluated the complementarity and/or associations between imaging and histopathological features in HNSCC [10][11][12][13][14][15], as well as in different malignancies, i.e. breast cancer, lung adenocarcinoma and glioma [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…However, their patient population underwent surgery, and sub-optimal delineation of only one imaging technique was performed. Although in advanced tumors SUV max /ADC min , SUV max /ADC mean and TLG/ADC min correlated with cellularity, Ki67 and HIF-1a [47], no prognostic tests were performed. Chan et al [21] found that a combination of PET heterogeneity (uniformity), DCE-MRI parameters and clinical risk factors was most predictive for LR and OS.…”
Section: Tablementioning
confidence: 99%
“…A multicenter and prospective study with more patients could be more representative of the population. Surov et al found that more complex PET- and DWI-based parameters proved useful to reflect several histopathological parameters ( 37 ). However, our study included only the conventional parameters, which might be one of the limitations of this research.…”
Section: Discussionmentioning
confidence: 99%